Implementasi Model Problem Based Learning Berbasis Audiovisual Untuk Meningkatkan Hasil Belajar IPAS Kelas V - Sari, Intan Permata; Sholikah, Octariana Hidayatus; Wahyuningtyas, Sri Endah (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
This research aims to describe learning activities and improve learning outcomes in Natural and Social Sciences (IPAS) in class V students using an audiovisual-based Problem Based Learning (PBL) model. The method used in this research is classroom action research (PTK) with research subjects of 26 students. Data collection techniques are carried out through observation and tests, while data analysis is based on the results of the cycle during the learning process. The research results show that the use of an audiovisual-based PBL model significantly increases student learning activities. Student learning activities in cycle I had an average of 2.7 (fairly good category), and increased to 3.8 (good category) in cycle II. Teacher activity also showed an increase from an average of 2.5 (fair category) in cycle I to 3.7 (good category) in cycle II. Apart from that, students' science and science learning outcomes also experienced a significant increase. In pre-action, students' classical completeness only reached 51% with an average score of 66. In cycle I, classical completeness increased to 65% with an average score of 75, and in cycle II it reached 95% with an average score of 90. Research This concludes that the audiovisual-based PBL model is effective in improving learning activities and science learning outcomes in fifth grade students.